Strongly orthogonal and uniformly orthogonal many-placed operations - Belyavskaya, G.; Mullen, G.L. (Algebra and Discrete Mathematics, 2006)
In [3] we have studied connection between orthogonal hypercubes and many-placed (d-ary) operations, have considered different types of orthogonality and their relationships. In this
article we continue study of orthogonality of many-placed operations, considering special types of orthogonality such as strongly
orthogonality and uniformly orthogonality. We introduce distinct
types of strongly orthogonal sets and of uniformly orthogonal sets
of d-ary operations, consider their properties and establish connections between them.